Natural Tourism Potential Assessment Model in Rembang Regency - Rizaldi, Artamevia Salsabila; Soesanto, Rayinda Pramuditya; Rizana, Afrin Fauzya; Rumanti, Augustina Asih (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2022)
This study identifies the criteria for developing natural tourism potential in Rembang Regency. There are problems, such as on the white sand beach of Wates. There are still attractions that have not been managed, namely the mangroves around the beach that have not been managed and around the tour. There are no lodgings such as hotels and guest houses for tourists, so for now, the distance to the beach can be accessed by vehicle because of quite a distance. To meet the requirements of tourist attraction, five criteria must be met based on the literature study: Attractions, Accommodations, Accessibility, Activities, and Amenities. After obtaining the criteria, a weighting will be carried out for each criterion based on 5A using the AHP approach. Based on the results obtained, it is known that the Accessibility criteria have the highest weight value, followed by the Amenity, Activities, Accommodation and Attractions criteria. Value modelling is carried out to calculate tourism feasibility according to standards.